Peran E-Learning dalam Meningkatkan Kualitas Pendidikan Agama Islam - Suranti Suranti (Jurnal Pendidikan Islam Indonesia, 2025)
The development of information and communication technology has brought significant changes in various aspects of life, including in the field of education. Islamic Religious Education (PAI), as an important subject at various educational levels, has also undergone transformation through the implementation of e-learning. This study aims to examine the role of e-learning in improving the quality of Islamic religious education. The methods used are literature review and observation of the implementation of e-learning in Islamic educational institutions. The results indicate that e-learning provides easier access to learning, flexibility in time and place, as well as a variety of more engaging and interactive teaching methods. Additionally, e-learning encourages increased motivation and better understanding of Islamic religious materials among students. However, challenges such as limited infrastructure and lack of teacher competence in using technology still need to be addressed to maximize the benefits of e-learning. Overall, e-learning plays an important role in enhancing the quality of Islamic Religious Education by offering more effective and efficient learning solutions in the digital era.